Funds of knowledge 2.0: towards digital funds of identity - Poole, Adam (Elsevier, 2017)
This article builds on the growing work on Funds of Identity by offering a conceptualisation of identity in relation to Vygotsky's concept of perezhivanie which is then situated within the discourse on digital identities. I also suggest how teachers and researchers could use avatars, digital representations of online users, as an identity text for drawing on and constructing students' Funds of Identity. In order to illustrate this approach, I briefly sketch an ongoing class-based research project called The Avatar Project. Overall, this article reaffirms and develops the argument that the Funds of Identity approach is an evolution of Funds of Knowledge. This thesis is encapsulated in the phrase, digital Funds of Identity: Funds of Knowledge 2.0.